Investigation of SRS conversion of XeCl laser emission in lead vapor, methane, and hydrogen; Journal of Russian Laser Research; Vol. 15, iss. 1 - Melchenko S. V. Sergey Vladimirovich; Panchenko A. N.; Tarasenko V. F. Victor Fedotovich; Evtushenko G. S. Gennady Sergeevich (1994, 1994)
В фонде НТБ ТПУ отсутствует